Indigenous Education: A Study of Resilience in the Tenganan and Baduy Luar Communities - Ginting, Eikel (Satya Widya: Jurnal Studi Agama, 2025)
Indigenous education implemented by the Tenganan and Baduy Luar communities is a form of education that is liberating and plays an important role in maintaining cultural identity and fighting the negative impacts of globalization. This education is not based on a structure of domination, but rather forms a collective critical consciousness that allows indigenous people to understand and maintain their traditional values. Unlike formal education which often focuses on one-way knowledge transfer, indigenous education in these two communities prioritizes a collective and relational learning process. In this study, Paulo Freire's theory of liberating education is used as an analytical framework, emphasizing the importance of critical consciousness and active participation in the educational process. Indigenous education in Tenganan and Baduy Luar has proven effective in facing the challenges of modernization and pressures from global capitalism, by emphasizing ecological balance and a harmonious relationship between humans and nature. Through education that is passed down orally and based on experience, these two communities are able to maintain the continuity of their culture amidst the changing times. The conclusion of this study shows that indigenous education functions as a tool of liberation that is not only relevant for indigenous communities, but can also be an alternative model in fighting marginalization and maintaining the integrity of cultural identity and environmental sustainability.